2017
DOI: 10.5552/drind.2016.1524
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Altitude Difference on Physical and Mechanical Properties of Scots Pine Wood Grown in Turkey - Sinop Province

Abstract: • In this study, the effect of altitude difference on the physical and mechanical properties of Scots pine (Pinus sylvestris L.) wood was investigated. For this purpose, nine SAŽETAK • U radu su prikazani rezultati istraživanja utjecaja nadmorske visine staništa na fi zikalno-mehanička svojstva drva običnog bora (Pinus sylvestris L.). Za istraživanje je odabrano devet stabala običnog bora u šamama pokrajine Sinop (u crnomorskoj regiji Turske) s lokacija različite nadmorske visine: 250 m (mala nadmorska visina)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The results show that the first axis has the highest correlation with tree-level traits and the second axis has the highest correlation with the traits wood properties, altitude and temperature. Comparable results were reported by Kiaei et al [11], Noshiro et al [18], Yılmaz et al [19] and Kaygin et al [23].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The results show that the first axis has the highest correlation with tree-level traits and the second axis has the highest correlation with the traits wood properties, altitude and temperature. Comparable results were reported by Kiaei et al [11], Noshiro et al [18], Yılmaz et al [19] and Kaygin et al [23].…”
Section: Discussionsupporting
confidence: 77%
“…In detail, the results of the wood anatomical studies show that, with increasing altitude, vessel diameters narrowed, vessel numbers increased and vessel and fiber length decreased. Kaygin et al [23] reported a significant relationship between wood oven-dry density and altitude difference for Scots pine (Pinus sylvestris). It worth mentioning that most studies mainly concentrated solely on wood properties on its own and ignored the relationship between wood properties and environmental growth traits.…”
Section: Introductionmentioning
confidence: 99%